Monetary policy and inequality: A two-way relation - Luzie Thiel (Philipps-University Marburg, School of Business and Economics, 2023)
We study the transmission of monetary policy in the presence of heterogeneous households and examine the implications when the share of constrained households is a function of monetary policy. We build an analytically tractable heterogeneous agent New Keynesian model (THANK) with an endogenous share of hand-to-mouth households. The transmission of monetary policy on aggregate demand is amplified in this setup by inequality between saver and hand-to-mouth households. The amplification effect depends on monopolistic rents (enhancing) and redistribution (mitigating). Unlike most THANK models, we refrain from the assumption of a full insurance steady state.
Keywords: E12; E21; E44; E52; E58; 330; Monetary Policy; Heterogeneous Households; Inequality; Aggregate Demand; Complementarity; Financial Conditions; Imperfect Insurance